Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2850.2011.01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' attitudes towards breastfeeding among women with schizophrenia in southern Israel

Abstract: Breastfeeding is the best source of nutrition for infants. Approximately half of women with schizophrenia become mothers, yet the issue of breastfeeding is often overlooked by the health professional community. The aim of this study was to survey attitudes among registered nurses regarding breastfeeding by schizophrenic women. Cross-sectional descriptive design was used involving a sample of nurses (40 midwives, 37 psychiatric and 33 postpartum) in two medical centres in southern Israel. The validated semistru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Consequently, mental health nurses are likely to encounter a significant number of breastfeeding women, or women who would like to breastfeed than is perhaps routinely acknowledged (Artzi‐Medvedik et al . 2012). Yet, there is good evidence to suggest that difficulties with breastfeeding can exacerbate post‐natal mental health issues (Chaput et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, mental health nurses are likely to encounter a significant number of breastfeeding women, or women who would like to breastfeed than is perhaps routinely acknowledged (Artzi‐Medvedik et al . 2012). Yet, there is good evidence to suggest that difficulties with breastfeeding can exacerbate post‐natal mental health issues (Chaput et al .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, mental health nurses work in arguably a greater variety of settings than many other healthcare professionals including home-based care, primary care, 24-hour emergency department liaison, intimate partner violence services and a panoply of inpatient units. Consequently, mental health nurses are likely to encounter a significant number of breastfeeding women, or women who would like to breastfeed than is perhaps routinely acknowledged (Artzi-Medvedik et al 2012). Yet, there is good evidence to suggest that difficulties with breastfeeding can exacerbate post-natal mental health issues (Chaput et al 2016;Dias & Figueiredo 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al (2005)'s qualitative study, women with EDs felt unhappy about their infants' continued dependency on them for nutrition 'I am annoyed that I have to carry on eating to provide milk for my baby'(Patel et al, 2005, p. 357). Though others were motivated to breastfeed as they believed this may help them to lose weight postnatally: 'I dread giving up breastfeeding because of the weight gain'(Patel et al, 2005, p. 357).3.7 | What are HCPs' attitudes towards supporting infant feeding in women with SMI?Two studies conducted in Israel and Greece focused on HCPs' attitudes towards breastfeeding among women with schizophrenia(Artzi-Medvedik et al, 2012; Sakellari et al, 2020). Staff included mental health nurses, midwives and health visitors.…”
mentioning
confidence: 99%
“…Staff included mental health nurses, midwives and health visitors. Two themes were generated from these two studies and are discussed under the following:3.7.1 | Overall positive attitudes from HCPs towards breastfeeding among women with schizophreniaThe majority of HCPs held positive views about breastfeeding among women with schizophrenia, with some variation between different staff groups Artzi-Medvedik et al (2012). found that midwives in Israel held the most positive views, while psychiatric nurses had the least positive views.…”
mentioning
confidence: 99%
See 1 more Smart Citation